2015
DOI: 10.1123/ijsnem.2014-0267
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Weight Loss Elicits Harmful Biochemical and Hormonal Responses in Mixed Martial Arts Athletes

Abstract: The purpose of this study was to compare biochemical and hormonal responses between mixed martial arts (MMA) competitors with minimal prefight weight loss and those undergoing rapid weight loss (RWL). Blood samples were taken from 17 MMA athletes (Mean± SD; age: 27.4 ±5.3yr; body mass: 76.2 ± 12.4kg; height: 1.71 ± 0.05m and training experience: 39.4 ± 25 months) before and after each match, according to the official events rules. The no rapid weight loss (NWL, n = 12) group weighed in on the day of the event … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
49
4
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 28 publications
7
49
4
3
Order By: Relevance
“…RWL has been a matter of concern for the medical community for over 40 years and its potential hazards have been recognized by at least three medical associations [3][4][5][6]. The list of potential negative effects associated with RWL is extensive, with some of the most severe and hazardous being: 1) severe dehydration [7][8][9]; 2) hormonal imbalance [10][11][12]; 3) increased muscle damage [12] which, in extreme cases, may lead to rhabdomyolysis and death [6]; 4) increased risk of injury during competition [13]. Therefore, RWL cannot be considered safe.…”
Section: Dear Editormentioning
confidence: 99%
See 2 more Smart Citations
“…RWL has been a matter of concern for the medical community for over 40 years and its potential hazards have been recognized by at least three medical associations [3][4][5][6]. The list of potential negative effects associated with RWL is extensive, with some of the most severe and hazardous being: 1) severe dehydration [7][8][9]; 2) hormonal imbalance [10][11][12]; 3) increased muscle damage [12] which, in extreme cases, may lead to rhabdomyolysis and death [6]; 4) increased risk of injury during competition [13]. Therefore, RWL cannot be considered safe.…”
Section: Dear Editormentioning
confidence: 99%
“…The literature indeed demonstrates that 5% is an approximation of the average weight loss for many combat athletes, but it is important to note that the range of weight loss is high. Consequently, a substantial proportion of athletes lose amounts of body mass even greater than the same ~15% that led those wrestlers to lose their lives [9][10][11][12][13][14][15][16][17][18][19].…”
Section: Dear Editormentioning
confidence: 99%
See 1 more Smart Citation
“…Short-term RED in sport is described as 1 month period, which is not the reality of MMA due to the fact that rapid weight loss occurs normally during a week3 and due to low frequency of fight by year. In this case, it is imprudent to indicate that it occurs in 100% of athletes and that it should affect performance or always generate health consequences although we agree that this procedure is not appropriate.…”
mentioning
confidence: 99%
“…Recent studies have shown the acute harmful effects of rapid weight loss (∼10%), involving lower glucose availability and higher catabolic expression,3 as well as lower serum testosterone 4. From a chronic point of view, some weight cyclers could adapt to weight loss procedures showing lower negative effects on performance,5 and exhibiting a little weight gain after a career in combat sports, which lasted 10 years 6.…”
mentioning
confidence: 99%